Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.fct.2014.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin exposure during the first 1000 days of life in rural South Asia assessed by aflatoxin B1-lysine albumin biomarkers

Abstract: Aflatoxin B1 is a potent carcinogen, occurring from mold growth that contaminates staple grains in hot, humid environments. In this investigation, aflatoxin B1-lysine albumin biomarkers were measured by mass spectrometry in rural South Asian women, during the first and third trimester of pregnancy, and their children at birth and at two years of age. These subjects participated in randomized community trials of antenatal micronutrient supplementation in Sarlahi District, southern Nepal and Gaibandha District i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
79
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 34 publications
8
79
0
2
Order By: Relevance
“…We found that AF exposure was nearly ubiquitous among a group of young children of around 12 months of age in southern Mexico, but serum AFB 1 ‐lysine adduct levels were considerably lower than those documented in young children in other regions. In Benin, mean exposure in children 16‐ to 37‐month old ranged from 2.48 to 25.06 pg AFB 1 ‐lysine/mg albumin (ELISA‐obtained levels in the Benin study were rescaled using a factor of 4.76 to make them comparable with the results in our study; Y. Gong et al, ; McCoy et al, ); in Bangladesh, the median was 13.79 pg AF B1‐lysine/mg albumin in 2‐year‐old children (Groopman et al, ).…”
Section: Discussionsupporting
confidence: 63%
“…We found that AF exposure was nearly ubiquitous among a group of young children of around 12 months of age in southern Mexico, but serum AFB 1 ‐lysine adduct levels were considerably lower than those documented in young children in other regions. In Benin, mean exposure in children 16‐ to 37‐month old ranged from 2.48 to 25.06 pg AFB 1 ‐lysine/mg albumin (ELISA‐obtained levels in the Benin study were rescaled using a factor of 4.76 to make them comparable with the results in our study; Y. Gong et al, ; McCoy et al, ); in Bangladesh, the median was 13.79 pg AF B1‐lysine/mg albumin in 2‐year‐old children (Groopman et al, ).…”
Section: Discussionsupporting
confidence: 63%
“…Additional factors related to stunting to investigate should include environmental enteric dysfunction (Campbell, Schulze, et al, ), potential roles of micronutrient deficiencies (e.g., zinc) and other possible exposures such as aflatoxin, as recently reported to be endemic in neighbouring countries of Nepal and Bangladesh (Groopman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Aflatoxin contamination can occur during pre-harvest or post-harvest. Due to poor storage conditions, post-harvest contamination has contributed to outbreaks that have killed hundreds and affected thousands in developing countries [2,3,4]. Chronic exposure to low levels of aflatoxin has been linked to child stunting and hepatosplenomegaly, and enlargement of the liver and spleen [4,5].…”
Section: Introductionmentioning
confidence: 99%